Nutrient and Sensory Quality of Soymilk Produced from Different Improved Varieties of Soybean - Ugochi, Nwoke Faith; Chukwuma, Umelo Munachiso; Nwanneoma, Okorie Josephine; Ndako,; Jummai, Khadijat; Nwabugo, Maduforo Aloysius (Pakistan Journal of Nutrition, 2015)
The study aimed to determine the most nutritionally and organoleptically suitable improved variety of soybean sample for soymilk production. Soymilk sample were extracted from different varieties of soybean namely; TGX-4482E, TGX-814496E, SAMSOY 1, SAMSOY 2, SAMSOY 3 for sample A, B, C, D and E, respectively. The processed soymilk samples were subjected to nutrient analysis using standard methods. Also sensory evaluation was carried out using another batch of extracted soymilk using 9-point hedonic scale to rate panellist preference for the organoleptic qualities of the soymilk products. The results were subjected to statistical analysis to determine whether significant difference existed between their nutrient compositions and also in the various organoleptic qualities. Results from the proximate analysis of soymilk showed that the crude protein values ranged from 4.52±0.03 to 4.84±0.02 with sample A (TGX4482E) having the highest value of 4.84±0.02 and SAMSOY 1 the least value of 4.52±0.03. TGX 4482E did not differ significantly from the other sample at (p>0.05). The moisture content ranged from 89.62±0.11 to 90.46. The % crude fat ranged from 1.98 to 2.17 with the highest recorded for TGX 4482E and the least SAMSOY 2. The Vitamin composition showed that the Vitamin B1 ranged from 0.058±0.00 to 0.074±0.00, vitamin C content ranged from 0.34±0.0 to 0.435±0.02. The mineral composition showed that TGX448-2E has the highest phosphorous of 89.63 mg/100 g and highest zinc content of 0.96 mg/100 g. SAMSOY 3 has the highest Iron content and TGX 81449E has the highest calcium content. Also sensory evaluation result revealed that SAMSOY 2 was mostly preferred. The study has shown that soymilk is a good source of macronutrient however, it also was observed that the sample highly preferred had lower nutritional quality when compared to others used in the study. There is need therefore to fortify the product with micronutrients so that it can conveniently serve as a good alternative to animal proteins.